Primary tumour growth in an orthotopic osteosarcoma mouse model is not influenced by analgesic treatment with buprenorphine and meloxicam. (October 2015) - Husmann, K; Arlt, M J E; Jirkof, P; Arras, M; Born, W; Fuchs, B
Little is known about the treatment of bone pain in animal models of bone cancer. In the present study, the orthotopic 143-B human osteosarcoma xenotransplantation model was used to address the following questions: (1) Can repetitive analgesic treatment extend the experimental period by prolonging the time to reach humane endpoints and (2) Does repetitive analgesic treatment affect bone tumour development and metastasis? The analgesics, buprenorphine and meloxicam, were either applied individually or in combination at 12 h intervals as soon as the animals began to avoid using the tumour cell injected leg. While control mice treated with NaCl showed continuous body weight loss, the major criterion previously for terminating the experiments, animals treated with analgesic substances did not. The control mice had to be sacrificed 26 days after tumour cell injection, whereas the groups of animals with the different pain treatments were euthanized after an additional eight days. Importantly, primary intratibial tumour growth was not affected in any of the experimental groups by any of the pain treatment procedures. Between days 26 and 34 after tumour cell injection an increase of about 100% of the number of lung metastases was found for the groups treated with buprenorphine alone or together with meloxicam, but not for the group treated with meloxicam alone. In summary, the results indicated that both buprenorphine and meloxicam are suitable analgesics for prolonging the experimental periods in an experimental intratibial osteosarcoma mouse model.